Potential Immune Modularly Role of Glycine in Oral Gingival Inflammation. (17th November 2013) - Schaumann, Teresa; Kraus, Dominik; Winter, Jochen; Wolf, Michael; Deschner, James; Jäger, Andreas
Abstract : Gingival epithelial cells (GECs) represent a physical barrier against bacteria and are involved in the processes of innate immunity. Recently, an anti-inflammatory and immune-modulatory effect of the amino acid glycine has been demonstrated. However, there is only little information about the immune-modulatory effects of glycine in oral tissues. This study aimed to investigate the existence and role of the glycine receptor in gingival tissue analyzing tissues/cells from extracted human molars via immunohistochemical analysis. In vitro, GECs were challenged by inflammatory conditions with IL-1 β alone or in combination with glycine and analyzed for cytokine expression of IL6/IL8 via real-time PCR. On protein level, the effect of nuclear translocalization of NF κ B protein p65 was analyzed using immunofluorescence analysis. A distinct proof of the GlyR in oral gingival tissue and keratinocytes could be demonstrated. Isolated challenge of the keratinocytes with IL-1 β as well as with glycine resulted in an upregulation of IL6 and IL8 mRNA expression and activation of NF κ B pathway. The presence of glycine in combination with the inflammatory stimulus led to a significant decrease in inflammatory parameters. These results indicate a possible anti-inflammatory role of glycine in gingival inflammation and encourage further research on the utility of glycine in the prevention or therapy of inflammatory periodontitis.